(untitled) (Journal of actual problems of jurisprudence, 2019)
In the case of the successful implementation of reforms and the necessary technical regulations will not only created a new technical legislation of the Kyrgyz Republic, but also the formation of a certain system of relationships between producers, consumers and the state in ensuring the safety of products and production processes.